EXPLORING THE IMPACT OF TEACHER SOCIAL IDENTITY ON MOTIVATIONAL ENHANCEMENT - Gvelesiani, Tamari (PROFESSIONAL STUDIES: Theory And Practice, 2024)
In the field of psychology, motivation is viewed as the process through which individuals prioritize incoming messages based on their needs and subsequently engage in behaviour accordingly. When exploring factors contributing to teachers' motivation, it becomes crucial to emphasize the role of teachers' social identity. Teachers with elevated social identity and group belonging levels often integrate didactic and innovative methods in their teaching practices, driven by their confidence in their abilities. These methods not only foster students' independence and autonomy but also enhance the learning environment. As part of the study, 405 teachers from both private and public schools in five diverse cities across Georgia took part in the quantitative survey. The convenience sampling method was employed throughout the research process; therefore, the results cannot be generalized to the population of teachers in Georgia. The study reveals that teachers perceive themselves and their colleagues similarly, indicating a strong collective identity within the teaching community, regardless of individual differences. Demographic factors such as teacher status, income, city, and education do not significantly affect this sense of belonging. Identified regulation emerges as the primary form of motivation among teachers, reflecting their perception of the importance of their profession. Moreover, there is a positive correlation between social identity and teacher motivation, suggesting that a stronger sense of belonging corresponds to higher motivation levels.